EARLY CHRISTIAN PRAYER AND IDENTITY FORMATION - C Stenschke (Acta Theologica)
Christoph Stenschke reviews a book from HVALVIK, R. & SANDNES, K.O. (eds.). WUNT 336. (Tübingen: Mohr Siebeck, 2014). Viii + 421 pp., ISBN 978-3-16-153520-8